Axillary lymph node metastases from thyroid carcinoma: Report of seven cases. Issue 4 (August 2021) - Suehiro, Atsushi; Nagahara, Kunihiko; Moritani, Sueyoshi; Omori, Koichi
Abstract: Objective: Axillary lymph node metastasis (ALNM) of well- or poorly-differentiated thyroid cancer is rare. Notably, there are only 14 single case reports available; therefore, the mechanism of metastasis is unclear at this point. Because we encountered seven cases at a single institution, we were able to infer the mechanism of ALNM of thyroid cancer. Methods: The seven cases treated at our institution were analyzed retrospectively. In addition, 14 cases reported from other institutions were reviewed. Results: All seven patients we treated and the 10 patients, among the 14, from other institutions were postoperative recurrences. All seven patients we treated had lymph node metastases near the venous angle, and invasive manipulation had been performed during the previous surgery. Conclusion: Therefore, we can presume that fibrosis at the venous angle caused by ablative surgery or tumor invasion could have resulted in anomalous lymphatic flow from the neck to the axilla. Hence, the subclavian region would probably need to be dissected besides axillary dissection.